Experiential Learning Model Based on Local Wisdom in Learning Islamic Cultural History - Purwowidodo, Agus (LETIGES, 2024)
Islamic Cultural History (SKI) learning must include cognitive aspects and applications in everyday life. The experiential learning model offers experiences that help students develop thinking skills to find the right solution to problems in the field. This study examines how the local wisdom-based experiential learning model influences the improvement of metacognitive skills, learning motivation, and learning outcomes in the subject of Islamic Cultural History (SKI) in grade V students of State Madrasah Ibtidaiyah (MI), who previously used more memorisation-based and less contextual learning methods. This study uses a quantitative method with a pretest-posttest control group experimental design, analysing the relationship between experiential learning strategies based on local wisdom, metacognition, motivation, and learning outcomes of grade V SKI students using MANOVA multivariate analysis and SPSS-26.0, with data collected through tests, questionnaires, and observations on elementary school students in Tulungagung Regency. The results of the study show that (1) there is an effect of the Experiential Learning model on improving students' metacognitive skills, (2) there is an effect on students' learning motivation, and (3) there is an effect on improving students' learning outcomes in the Islamic Cultural History course. Theoretically, this study confirms that the experiential learning model effectively enhances metacognition for independent learning and critical thinking. At the same time, the results indicate that Madrasah Ibtidaiyah (MI) should adopt this model to improve student engagement and learning outcomes, with support from teachers and madrasah principals.